Coming out of the woods. Do local support services influence the propensity to report sexual violence? - Denti, Daria (2021)
Sexual crimes against women are severely underreported to the police, allowing for impunity of perpetrators. Observers suggest that a stimulus towards reporting the crime comes from nearby support services for victims of sexual offences -like refuges and advisors. Still, the evidence about the effects of nearby support on the reporting of sexual crimes remains scattered and mainly qualitative. This paper provides quantitative evidence on this effect, by exploiting the uneven geography of local support services which resulted in the UK after the introduction of the austerity program. Findings highlight a positive net effect of the provision of local support services on the victims’ propensity to report. The positive effect holds also in the aftermath of a space-neutral high-impact media campaign empowering women to report sexual violence. This evidence relates to relevant policy implication, given that in some countries the austerity-driven cuts to public budgets have reduced and dispersed the local availability of support services, making digital support and/or helpline the only available options in many places